Otoacoustic emission (OAE) features in newborns at Dr. Kariadi Central Genetal Hospital, Semarang, Indonesia - Rikha Liemiyah; Dwi Marliyawati; Gatot Irawan; Arsita Eka Rini; Nuniek Wulansari; Muyassaroh Muyassaroh (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
The joint committee on infant hearing (JCIH) recommends the detection and intervention of hearing impairment in newborns. Dr Kariadi Central General Hospital, Semarang, Indonesia is a referral hospital in Central Java province that has implemented an early detection program for hearing lossin newborns. Screening or early detection using otoacoustic emissions (OAE). This study aimed to find out the description of OAE in newborns at Dr. Kariadi Central General Hospital, Semarang. This research was a descriptive analytic using secondary data the OAE results on newborns with or without risk factors (FR) who are treated at Dr. Kariadi Central General Hospital, Semarang in 2020. The result of OAE pass meant that the outer hair cell (OHC) was functioning properly in both ears while refer was if the OHC in one ear or both was not functioning properly. Total 1338 newborns with and without FR whose OAE pass resulted as much as 1297 (97%) and refer 41 (3%). Most risk factors were low birth weight 331 (42%) with the results of OAE pass 312 (94.3%), and refer 19 (5.7%). In conclusion, this study shows that OAE passed in 97% of newborns.